Nonselective beta-blockers in primary prophylaxis of esophageal variceal bleeding in patients with ascites waitlisted for liver transplantation - V. L. Korobka; V. D. Pasechnikov; R. V. Korobka; E. S. Pak; A. M. Shapovalov; D. V. Pasechnikov (Вестник трансплантологии и искусственных органов, 2023)
Objective: to determine the efficacy of non-selective beta-blockers (NSBBs) in the primary prevention of bleeding esophageal varices and to assess their impact on the survival of patients with ascites enrolled in the liver transplant waiting list (LTWL).Materials and methods. We carried out a retrospective comparative study of cirrhotic patients with severe ascites and esophageal varices without bleeding before enrollment in the LTWL. Primary prophylaxis of variceal bleeding included the use of NSBBs (n = 97, group 1). These drugs were not used in the other patients (n = 91, group 2).Results. There were no significant differences between the groups in terms of clinical, laboratory and demographic parameters, MELD scores and Child-Turcotte-Pugh (CTP) classes for cirrhosis. Patient groups included in the study had no significant differences with respect to incidence of medium- and large-sized varices and incidence of severe ascites. Bleeding incidence was significantly lower in the NSBBs group than in the non-NSBBs group (52.6% and 95.6%, respectively, p = 0.0001).Conclusion. NSBBs constitute an efficacious therapy in primary prophylaxis of esophageal variceal bleeding, thereby saving life and preventing delisting of patients with ascites from the LTWL.